Top‐100 cited articles on Guillain‐Barré syndrome: a bibliometric analysis. Issue 4 (7th December 2016) - Kim, Jee‐Eun; Kim, Jong Kuk; Park, Kang Min; Kim, Yerim; Yoon, Dae Young; Bae, Jong Seok
Abstract: Since the first description of Guillain‐Barré syndrome (GBS) 100 years ago, the concept of this syndrome has changed remarkably. The purpose of our study was to identify and characterize the most‐cited articles that have contributed to advancing the understanding of GBS. Based on the database of Journal Citation Reports, we selected 554 journals that were considered as potential sources of reports on studies related to clinical neurology and general medicine. The Web of Science search tools were used to identify the most‐cited articles relevant to GBS or other variants in the selected journals. Of the selected articles, 18 were review articles and the remainder were original articles or included only a few case series. Among the original articles, 13 described basic research associated with immunological pathogenesis involving anti‐ganglioside antibodies. Most of the original studies (42/64, 66%) published after 1990 evaluated anti‐ganglioside antibodies that mediated axonal GBS or Miller Fisher syndrome, with only a small number of the papers involving electrodiagnostic medicine (n = 4). Our bibliometric analysis has yielded a detailed list of the top‐100 cited articles in the field of GBS.